PENGARUH TERAPI TARI TERHADAP PENURUNAN TINGKAT STRES PADA ANAK - Fitriatul Masruroh; Rizki Wiji Nugroho (AL IHSAN: Jurnal Pendidikan Islam Anak Usia Dini, 2021)
The study aims to test the influence of dance therapy with reduced stress levels. The subjects in this study were students of SMAN 1 BANGIL. The sample count in this study was 30 male and female students, taken with Purposive Random Sampling technique. Statistical analysis used for hypothesis testing is a correlation of t-test and replay. The results of the analysis obtained F = 13,122, R = 0.213 with p = 0.001 (p<0.01) means there is a very significant influence between dance therapy and decreased stress levels in adolescents. The analysis result between A1 – A2 obtained t = 3,622 with p = 0.001 (p<0.01), average A1 = 62,267 and average A2 = 45,633 which means A1 > A2. This shows there is a very significant difference between before being given dance therapy (pre-test) and after being given dance therapy (post-test) where the level of stress in adolescents decreases after being given dance therapy.